2006
DOI: 10.1080/00016340600645255
|View full text |Cite
|
Sign up to set email alerts
|

Women's preference on mode of delivery in Southern Italy

Abstract: A high rate of women wish to give birth by cesarean section. This is probably an expression of the changes in society's attitudes. However, more careful attention to the psychological aspects and more personalized information about pregnancy and delivery could reduce this maternal demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 19 publications
6
29
1
1
Order By: Relevance
“…Meanwhile study conducted in Norway by Fuglenes et al [13] to investigate cesarean section preference who found that 85.6% of pregnant women were working, and Mancuso et al [40] who study delivery mode preference in Southern Italy and reported that 62.3% of pregnant women were employed.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile study conducted in Norway by Fuglenes et al [13] to investigate cesarean section preference who found that 85.6% of pregnant women were working, and Mancuso et al [40] who study delivery mode preference in Southern Italy and reported that 62.3% of pregnant women were employed.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that women experiencing intense fear are at greater risk of requiring acute caesarean section in comparison to women who do not experience FOC (Adams, Eberhard-Gran, Esklid, 2012). Other studies have indicated that FOC among multiparas is a factor in an increased ratio of caesarean section by request (Mancuso et al, 2006;Sydsjö et al, 2012;Räisänen et al, 2014;Fenwick et al, 2015). In Finland, Sweden and the United Kingdom, FOC is the main reason for caesarean section in 7-22% of all labors.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological "disabling" fear of childbirth [7] is felt in about 6%-10% of the pregnant women [4,5,[8][9][10][11]. Studies have shown that fear of childbirth has a significant impact on delivery outcome [12], resulting in a dramatic increase of cesarean births [8,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%